Enzymatic synthesis and purification of diacylglycerols from mutton tallow and hemp seed oil - Malgorzata Katarzyna Kowalska; Magdalena Wozniak; Serge Tavernier (Polskie Towarzystwo Farmaceutyczne, 2023)
Abstract: Production of preparations based on natural ingredients has become a priority in the cosmetic and pharmaceutical industries. The novelty of the study was to present a possible method for obtaining pure diacylglycerols (DAG) from natural raw materials like fats (hemp seed oil and mutton tallow). We have determined the optimum water content for enzymatic interesterification to shift the reaction equilibrium towards hydrolysis and obtain the highest DAG formation yield. Then, DAG were separated and purified by column chromatography. Raw fats were characterized by fatty acids composition and their positional distribution using gas chromatography. Triacylglycerols, diacylglycerols, monoacylglycerols and free fatty acid contents were determined using gel permeation chromatography. The main fatty acids found in sn-2 MAG of hemp seed oil was linoleic acid, which was followed by oleic acid. Saturated fatty acids in hemp seed oil's TAG showed preference for the outer sn-1,3 positions. For mutton tallow, the majority of oleic acid were found at sn-2 position. The optimum water content applied during enzymatic interesterification for DAG formation was estimated to be 2.0 % w/w, using the following conditions: 5 % w/w of catalyst, 200 rpm, 60 °C, 6h. DAG yield was 27 %. Purification of the mutton tallow-based and hemp seed oil-based DAG yielded with 83 % w/w and 82 % w/w, respectively. High purity DAG could be applied as effective emulsifiers in food, cosmetic or pharmaceutical emulsions.